2022
DOI: 10.3389/fped.2022.909962
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Maternal and Neonatal Microbiota in Spontaneous Preterm Birth: A Pilot Study

Abstract: The newborn’s microbiota composition at birth seems to be influenced by maternal microbiota. Maternal vaginal microbiota can be a determining factor of spontaneous Preterm Birth (SPPTB), the leading cause of perinatal mortality. The aim of the study is to investigate the likelihood of a causal relationship between the maternal vaginal microbiota composition and neonatal lung and intestinal microbiota profile at birth, in cases of SPPTB. The association between the lung and/or meconium microbiota with the subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Specifically, at the time of intubation, premature infants who developed BPD had lower bacterial diversity than those who did not develop BPD, as estimated by the number of observed species and the Shannon diversity index. This finding is supported by Tirone et al [ 28 ] who also observed a slight reduction, although not statistically significant, in the Shannon diversity index in BALF samples from infants with BPD. Tirone and colleagues did not identify a characteristic microbiological signature linked to BPD development at either the genus or phylum level.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Specifically, at the time of intubation, premature infants who developed BPD had lower bacterial diversity than those who did not develop BPD, as estimated by the number of observed species and the Shannon diversity index. This finding is supported by Tirone et al [ 28 ] who also observed a slight reduction, although not statistically significant, in the Shannon diversity index in BALF samples from infants with BPD. Tirone and colleagues did not identify a characteristic microbiological signature linked to BPD development at either the genus or phylum level.…”
Section: Resultssupporting
confidence: 70%
“…Tirone et al [ 28 ] demonstrated that, while the vaginal microbiota of mothers with a spontaneous preterm birth (SP PTB ) showed a significant difference in alpha diversity, marked by a decrease in Lactobacillus and an increase in Proteobacteria abundance, there were no significant differences in alpha e beta diversity between the neonatal bronchoalveolar lavage fluid (BALF) samples of the SP PTB group and the medically indicated preterm birth (MI PTB ) group. Regarding chorioamnionitis, Lohman et al [ 1 ] also reported that there were no statistically significant differences in bacterial diversity in endotracheal aspiration samples from newborns with and without exposure to chorioamnionitis, although they noted a trend toward decreased diversity in those infants who had been exposed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite advances in neonatal care, the rates of preterm births have not significantly decreased worldwide in recent years, highlighting the need for a deeper understanding of its etiology [ 3 , 4 ]. Emerging research has increasingly pointed to the role of the vaginal microbiota in maternal and neonatal health, suggesting a significant association between microbial dysbiosis and adverse pregnancy outcomes, including preterm birth [ 5 , 6 ]. The vaginal microbiome, a complex ecosystem of bacteria, varies widely among women and changes throughout pregnancy, influenced by factors such as genetics, environment, and lifestyle [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…During pregnancy, the gut microbiota primarily defends the health of the mother, for example, by helping her not to develop gestational diabetes, and at the same time, it also preserves that of the child who will be exposed to the first “transfer” of microorganisms at the time of birth[ 32 ]. The vertical transmission of the microbiota from mother to fetus, which appears to begin during intrauterine life, contributes to the development of the child’s gastrointestinal microbiota[ 33 ]. Going toward the third trimester, the relative abundance of some bacteria that are then transferred to the newborn in the peripartum (in the case of vaginal birth) increases: In fact, the child’s gut microbiota consists of 22% bacteria derived from the mother’s gut microbiota, particularly Bifidobacteria , Bacteroides , and Escherichia coli [ 31 ].…”
Section: Introductionmentioning
confidence: 99%